On the Occurrence of GPS Signal Amplitude Degradation for Receivers on Board LEO Satellites - Chao Xiong; Ji‐Sheng Xu; Claudia Stolle; Jose van denIjssel; Fan Yin; Guram N. Kervalishvili; Franz Zangerl (Space Weather)
Abstract Transient signal loss of the global positioning system (GPS) has been frequently observed by receivers on board the European Space Agency's Swarm mission when the satellites encounter ionospheric plasma irregularities. In this study we provided the first comparison of the GPS signal amplitude degradations from receivers on board low Earth orbiting satellites at different altitudes. Intense carrier phase variations but almost no amplitude fades (less than 2 dB Hz) are observed when the spaceborne receiver lies right inside the ionospheric plasma irregularities, like the case for the Swarm and CHAMP satellites flying at about 400–500 km. This indicates that the strong phase variation, but not the amplitude fades, causes the receivers to stop tracking the GPS signals. When the receiver is located 100–200 km below the slab of plasma irregularities, like the case for the GOCE satellite flying at about 250 km, signal amplitude fades exceeding 10 dB Hz are observed, in addition to strong phase variation. Our results suggest that a considerable distance of the receiver to the plasma irregularity slab is needed to affect the Fresnel diffractive process and further causes GPS signal amplitude fades.